2019
DOI: 10.5194/isprs-annals-iv-4-w8-27-2019
|View full text |Cite
|
Sign up to set email alerts
|

Raise the Roof: Towards Generating Lod2 Models Without Aerial Surveys Using Machine Learning

Abstract: <p><strong>Abstract.</strong> LoD2 models include roof shapes and thus provide added value over their LoD1 counterparts for some applications such as estimating the solar potential of rooftops. However, because of laborious acquisition workflows they are more difficult to obtain than LoD1 models and are thus less prevalent in practice. This paper explores whether the type of the roof of a building can be inferred from semantic LoD1 data, potentially leading to their free upgrade to LoD2, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
0
20
0
1
Order By: Relevance
“…Apart from this, most of the buildings in the city of Liege have pitched roofs. The potential of roof greening is relatively lower than other cities (Biljecki, Dehbi, 2019;Silva et al, 2017), mainly due to less number of flat roofs. Building stock in Wallonia region in general and in Liege is very old (Singh et al, 2013), resulting in large number of pitched roofs.…”
Section: Discussionmentioning
confidence: 91%
“…Apart from this, most of the buildings in the city of Liege have pitched roofs. The potential of roof greening is relatively lower than other cities (Biljecki, Dehbi, 2019;Silva et al, 2017), mainly due to less number of flat roofs. Building stock in Wallonia region in general and in Liege is very old (Singh et al, 2013), resulting in large number of pitched roofs.…”
Section: Discussionmentioning
confidence: 91%
“…As a result, they have reached a mean absolute error of 0.8 m in the inferred heights. Biljecki and Dehbi (2019) demonstrated that it is possible to predict the roof types from lower LoD (i.e., LoD0 and LoD1) datasets and to generate LoD2 models without roof measurements. They achieved an accuracy of 85% of the roof type from sparse data using a multiclass classification and 92% accuracy in predicting whether a roof is flat or not.…”
Section: Machine Learning Methodsmentioning
confidence: 99%
“…Untuk objek bangunan, CityGML mendefinisikan tingkat perincian dari LOD0 sampai dengan LOD4. Secara umum, LOD tinggi lebih diinginkan dibandingkan dengan LOD rendah (Biljecki & Dehbi, 2019). Namun, penggunaan LOD yang lebih detail tidak menjamin peningkatan kualitas hasil analisis yang dilakukan dengan menggunakan model tersebut, dikarenakan terdapat faktor kesalahan lain seperti tingkat akurasi akuisisi data geometri (Biljecki et al, 2018).…”
Section: Pendahuluanunclassified